Bespoke supply chain resilience facilitated by dedicated and shared resources - Florian Lücker (Asian Development Bank Institute (ADBI), 2023)
In this paper, we offer a characterization of resilience-enhancing measures. We argue that resilience-enhancing measures are either based on using dedicated resources (referred to as "dedicated resilience levers") or on using shared resources (referred to as "shared resilience levers"). By dedicated resources, we mean resources that are provided only for the purpose of building resilience. In contrast, shared resilience levers are based on using shared resources. By shared resources, we mean resources that are not only used for risk mitigation but also serve another purpose, such as helping to better meet customer demand without disruption. We argue that shared resilience levers are particularly helpful for supply chains that focus on cost-efficiency and produce basic/functional products. In contrast, dedicated resilience levers are particularly helpful for supply chains that are less exposed to cost pressure and that produce innovative products. Further, we discuss how the supply chain finance solution reverse factoring can be considered a shared resource that helps build resilience and efficiency simultaneously. We provide an overview of past and future research directions and a conclusion.
Keywords: M1; 330; supply chain resilience; supply chain efficiency; shared resources; flexibility